ASSET BASED COMMUNITY DRIVEN DEVELOPMENT METHOD FOR AGROTOURISM DEVELOPMENT ON INTEGRATED FARMING - Muhammad Ridwan Syah; Muhammad Askari Zakariah; Muhammad Zakariah; Muhammad Asra Azis (Jurnal Ekonomi Bisnis Syariah, 2018)
This community based research aim to determined effect asset based community driven development (ABCD) method for agrotourism development on integrated farming system were done in Mowewe district, East Kolaka Regency. Qualitative method were used participant observation developed. Approach stage of ABCD method for agrotourism development on integrated farming system are: discovering strengths, organizing and mapping, lingking and mobilizing, community driven initiatives and sustaining the process. Simulation model agrotourism development were tested during one week, with Student group from Islamic Boarding School and Integrated Islamic School Al-Mawaddah Warrahmah to done Rihlah Ilmiah (Programs to support agrotourism development). Concluded that ABCD method can accelerate agrotourism development on integrated farming system.